THE IMPACT OF DIGITAL TRANSFORMATION ON BANK PROFITABILITY: THE MEDIATING ROLE OF FINANCIAL INNOVATION - AN APPLIED STUDY ON IRAQI PRIVATE BANK - Muzna Ayal Fttnan (PT. Antis International Publisher, 2026)
Objective: The research paper will analyze the effect of the digital transformation on the profitability of Iraqi private banks and will test the mediating effects of financial innovation. Method: The data were obtained with the help of a structured questionnaire filled out by the bank workers in September to December 2025, which resulted in 191 valid answers. The measurement model was found to be very reliable and sufficient wherein the constructs Cronbach alpha was 0.814-0.922 and the overall instrument was 0.905 with high KMO values and significant Bartlett test values ensuring construct validity. Results: The descriptive outcomes showed that the perceived level of digital transformation and financial innovation was high, whereas perceived profitability improvement was positive but lower, which was adjective performance realization. Path analysis has verified that digital transformation has a great boosting effect on financial innovation and profitability improvement directly. There was also a noteworthy positive correlation between financial innovation and profitability and bootstrapped mediation on the indirect effect showed a significant indirect effect, so partial mediation occurred. The structural model provided significant variance in financial innovation and profitability, and diagnostic tests provided model suitability and fit. Novelty: The results indicate that the benefits of digital initiatives on profitability are not only determined by the digitization of operations and channels but also the ability of the bank to convert digital potential in novel financial products and the remodel of service procedures. The paper offers empirical conclusions to managers who want to integrate digital investments on quantifiable financial performance in the Iraqi banking industry.